The impact of salvage radiotherapy initiation at PSA ≤ 0.5 ng/ml on metastasis‐free survival in patients with relapsed prostate cancer following prostatectomy. Issue 2 (31st October 2022) - Lee, Emerson E.; Singh, Tanmay; Hu, Chen; Han, Misop; Deville, Curtiland Jr.; Halthore, Aditya; Greco, Stephen; Tran, Phuoc; DeWeese, Theodore; Song, Daniel Y.
Abstract: Background and Purpose: Salvage radiation therapy (SRT) is indicated for biochemical failure after radical prostatectomy. Prior data have shown that initiation of SRT at lower PSA levels improves subsequent biochemical control, yet given the long natural history of prostate cancer questions remain regarding optimal timing of SRT. We analyzed the impact of prostate specific antigen (PSA) level at time of salvage radiotherapy with regard to both biochemical relapse‐free (bRFS) as well as metastasis‐free survival (MFS) in patients with biochemically recurrent prostate cancer. Methods: Using prospective institutional tumor registry data, univariate and multivariable‐adjusted Cox proportional hazards models were constructed to assess association between outcomes and clinical and pathologic prognostic features, including pre‐SRT PSA, interval from prostatectomy to SRT, androgen deprivation therapy (ADT), and adverse pathologic features. Results: We identified 397 patients who received salvage RT between 1985 and 2016: 187 (45.8%) received SRT initiated when pre‐RT PSA was ≤0.5 ng/ml; 212 (52.0%) patients had pre‐SRT PSA > 0.5 ng/ml. Independent of pathologic risk status and ADT use, pre‐SRT PSA ≤ 0.5 ng/ml was the most significant predictor of bRFS (HR 0.39, 95% CI [0.27, 0.56]) as well as MFS (HR = 0.58, 95% CI [0.37, 0.91]). Seminal vesicle invasion was also associated with shorter interval to biochemical failure, HR = 1.79, 95% CI [1.07, 2.98], and eventual metastases, HR = 2.07, 95% CI [1.14, 3.740]. Conclusions: Initiation of salvage RT while PSA levels remain ≤0.5 ng/ml was associated with improved MFS. Consideration for salvage RT initiation while PSA levels remain low is warranted to minimize risk of future prostate cancer metastasis.